The long-lasting effects of experiencing communism on attitudes towards financial markets - Christine Laudenbach; Ulrike Malmendier; Alexandra Niessen-Ruenzi (Leibniz Institute for Financial Research SAFE, 2024)
We show that exposure to anti-capitalist ideology can exert a lasting influence on attitudes towards capital markets and stock-market participation. Utilizing novel survey, bank, and broker data, we document that, decades after Germany's reunification, East Germans invest significantly less in stocks and hold more negative views on capital markets. Effects vary by personal experience under communism. Results are strongest for individuals remembering life in the German Democratic Republic positively, e. g., because of local Olympic champions or living in a "showcase city". Results reverse for those with negative experiences like religious oppression, environmental pollution, or lack of Western TV entertainment.
Keywords: D14; D83; D91; G41; P10; P26; P34; P36; 330; Capital markets; Anti-capitalist Ideology; Life-time Experiences; Stockmarket Participation